VERBA TRANSITIF DALAM MAJALAH ONLINE PATRIOTIK LPM UNIVERSITAS BATANGHARI EDISI 17 OKTOBER-DESEMBER TAHUN 2019 - Rahmat Hidayat; Abdoel Gafar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research is to describe the forms of transitive verbs including transitive with two nouns as arguments and realization of object and agent case, ditransitive verbs and ambitransitive verbs in the online magazine patriotik LPM Batanghari University October-December 2019 issue. This research includes qualitative descriptive. The results of the research concluded that researcher found forty-four transitive verb sentences in the online magazine patriotik LPM Batanghari University October 17- December 2019 issue. The sentences are grouped by verb forms i.e. transitive with two nouns as arguments and realization of object and agent case, ditransitive verbs and ambitransitive verbs. Based on the results of the analysis in the online magazine patriotik, there are seven transitive with two nouns as arguments and realization of object and agent cases, twenty-seven ditransitive verbs, and twenty-one ambitransitive verbs.Keywords: transitive verb, ditransitive verb